If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9y + -2)(3y + 5) = 0 Reorder the terms: (-2 + 9y)(3y + 5) = 0 Reorder the terms: (-2 + 9y)(5 + 3y) = 0 Multiply (-2 + 9y) * (5 + 3y) (-2(5 + 3y) + 9y * (5 + 3y)) = 0 ((5 * -2 + 3y * -2) + 9y * (5 + 3y)) = 0 ((-10 + -6y) + 9y * (5 + 3y)) = 0 (-10 + -6y + (5 * 9y + 3y * 9y)) = 0 (-10 + -6y + (45y + 27y2)) = 0 Combine like terms: -6y + 45y = 39y (-10 + 39y + 27y2) = 0 Solving -10 + 39y + 27y2 = 0 Solving for variable 'y'. Factor a trinomial. (-5 + -3y)(2 + -9y) = 0Subproblem 1
Set the factor '(-5 + -3y)' equal to zero and attempt to solve: Simplifying -5 + -3y = 0 Solving -5 + -3y = 0 Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3y = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3y = 0 + 5 -3y = 0 + 5 Combine like terms: 0 + 5 = 5 -3y = 5 Divide each side by '-3'. y = -1.666666667 Simplifying y = -1.666666667Subproblem 2
Set the factor '(2 + -9y)' equal to zero and attempt to solve: Simplifying 2 + -9y = 0 Solving 2 + -9y = 0 Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -9y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -9y = 0 + -2 -9y = 0 + -2 Combine like terms: 0 + -2 = -2 -9y = -2 Divide each side by '-9'. y = 0.2222222222 Simplifying y = 0.2222222222Solution
y = {-1.666666667, 0.2222222222}
| Log(7x)=3.5 | | E*-3x=7.1 | | 3t-4=4t+16 | | 3x+31=12x-559 | | 17y=3x-19 | | (9+9)=(8-8) | | 10x-63=11 | | 8x^2-9x+k=0 | | 7x-2x-3x+2.73=4.49 | | 3x-5=-41 | | 9p-7= | | z^2+56x-1920=0 | | 7x+12y=12 | | z/-4=11-5 | | 0.7x+0.5=0.9x-1.1 | | 5x-6y=19fory | | 6(3+4x)-8=202 | | 4z/10-1=-8 | | 28-4*X=8 | | 3(4-2n)=2(7-n) | | 0.5/6=120/x | | 5x=12+2y | | 5/x=6/684 | | 3x+5x=150 | | 9-(2y-8)=6-3y | | 10m-26=4 | | -16(0)+128(0)+1680= | | 2x^3-3x=120 | | 2(n+3)=6(n-4) | | 2lm(3x)=8 | | 0=2400/x^2 | | x^2+-12x+36=0 |